Oral Health of Haemodialysed Patients with Chronic Renal Failure - E. Lenčová; A. Kalabisová; M. Ságová; Z. Broukal; S. Sulková; J. Dušková (Česká Stomatologie a Praktické Zubní Lékařství, 2005)
The aim of the study was to assess oral health of haemodialysed patients with chronic renal failure.The authors examined 64 patients (mean age 63.5 years). DMFT, CPITN and dental treatment need were determined. The obtained data were compared to those of a survey on oral health status of elderly people in the Czech Republic, 2002 [1].In the examined group, 74.9 % of patients had their own teeth, 54.5 % required dental treatment. Mean DT amounted to 2.26 per person, MT 15.65 and FT 7.97. CPITN could be assessed in 60 % of persons, in 64.82 % of sextants CPI score 1 to 3 was found. In dialyzed patients, significantly higher prevalence of edentulousness, higher number of DT and lower prevalence of periodontal tissues inflammation (P